Comparison of Drug Regimens (Sofosbuvir + Velpatasvir vs Sofosbuvir + Daclatasvir) in Treatment of Chronic HCV Patients in Terms of Efficacy and Safety - Mehran Farzand, Siraj-ud-Din, Abdul Mudabbir Rehan, Shafqat ur Rehman Orakzai, Humaira Rahim, Ihsan Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hepatitis C is a viral infection that can lead to liver cirrhosis if not treated properly. Objective: The aim of this study was to compare the drugs regimens (Sofosbuvir + velpatasvir vs Sofosbuvir + daclatasvir) in treatment of chronic HCV patients in terms of efficacy and safety Material and Method: The present descriptive multicentre study was conducted at MMC, DHQ hospital Kohat, AWKUM, KUST from January 2023 to June 2023 after taking approval from the research team of the hospital. Sample size was calculated using the WHO calculator. A total of 170 individuals of both genders and different age groups (ranged 18-60) years with compensated liver cirrhosis and chronic hepatitis C were included. The study participants were divided in to groups A and B equally. Group B got 400 mg plus 60 mg of daclatasvir in separate pills, whereas Group A had 400 mg of sofosbuvir plus 100 mg of velpatasvir in a single pill for 12 weeks. On HCV RNA fragments, hospital RT-PCR identified chronic hepatitis C. HCV RNA levels > 50 copies for six months, as determined by RT-PCR, indicated a chronic infection. SVR12 shown therapeutic efficacy after 12 weeks. The viral load of HCV was less than 50 IU/ml. After twelve weeks of treatment, SVR12 or responders appeared. SPSS version 23 was used for data analysis and were presented in frequencies and percentages. Results: The study participants were divided in to groups A and B and each group had 85 individuals. In A group females were 45(52.9%) and male were 40(47%) and in group B female were 38(44.7%) and male were 47(55.2%). the mean age of the study population in group A was 5.14years and group B was 4.27 years. The sustained virologic response rate was higher for sofosbuvir and velpatasvir than for daclatasvir. The 78 participants (91.7%) in group A had the SVR 12 rate, compared to 73 individuals (85.8%) in group B. Between groups A and B, the end of treatment response (ETR) was attained by 79 (92.9%) and 75 (88.2%), respectively. The major adverse effects in group A were head ache 11(12.9%), Fatigue10 (11.7%) and Nausea 6 (7%) and in group these were oral ulcer 13(15.2%), skin rashes 11(12.9%) and Epigastric discomfort 7(8.2%). Conclusion: The current study concluded that the group receiving velpatasvir and sofosbuvir had a longer-lasting viral response than the group receiving daclatasvir and sofosbuvir. Keywords: Drug regimens; Sofosbuvir; Velpatasvir; Sofosbuvir; Daclatasvir; Treatment; HCV